1991
DOI: 10.1038/ki.1991.19
|View full text |Cite
|
Sign up to set email alerts
|

Glycolate determination detects type I primary hyperoxaluria in dialysis patients

Abstract: The detection of type I primary hyperoxaluria is based on the finding of exceedingly high oxalate excretion which is associated with increased glycolate excretion. The differential diagnosis of this disease may become a difficult task once end-stage renal disease (ESRD) and anuria have supervened. The various procedures thus far proposed to obviate this circumstance are complex, inaccurate or not reproducible. In this paper we propose the accurate liquid chromatographic determination of glycolate in blood and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

1992
1992
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 22 publications
0
16
0
2
Order By: Relevance
“…that is 310± 126 umol/24 h [37], Increased oxalate appearance has been reported in a previous study on dialy sis patients [12], and pyridoxine deficiency, which is referred to as being common in this setting [38], has been implicated in its pathogenesis. Our patients exhibited no abnormality in oxalate metabolism, and pyridoxine deficiency was un likely to occur, as also supported by normal levels of plasma glycolate [39]. Instead, the close correlation of OxAR with both PGR and Gurea, suggested that nitrogen balance-relat ed or nutritional factors might be common determinants of oxalate metabolism.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…that is 310± 126 umol/24 h [37], Increased oxalate appearance has been reported in a previous study on dialy sis patients [12], and pyridoxine deficiency, which is referred to as being common in this setting [38], has been implicated in its pathogenesis. Our patients exhibited no abnormality in oxalate metabolism, and pyridoxine deficiency was un likely to occur, as also supported by normal levels of plasma glycolate [39]. Instead, the close correlation of OxAR with both PGR and Gurea, suggested that nitrogen balance-relat ed or nutritional factors might be common determinants of oxalate metabolism.…”
Section: Discussionmentioning
confidence: 88%
“…Second, plasma levels above the saturation threshold of calcium oxalate were measured in the very minority of the tested samples, and in no instance was this threshold ex ceeded more than 1.5 times. Third, as drawn in figure 2, preand postdialysis plasma levels of oxalate were far below those measured by us by the same IC technique (i.e., 162±24 and 60.4±14.0 pmol/l, pre-and postdialysis, re spectively) in patients on RDT and with primary hyperoxal uria, in which systemic oxalosis had been clearly document ed [39].…”
Section: Discussionmentioning
confidence: 99%
“…Even after the end-stage of renal failure and anuria, the molecular diagnosis of PH1 can be achieved by targeting glycolate (Marangella et al, 1991) and oxalate in the blood. The quantification of oxalate should be done carefully to avoid the generation of any oxalate after blood sampling (France, Windleborn, & Wallace, 1985;Costello & Landwehr, 1988).…”
Section: A Urinary Stones and Primary Hyperoxaluriasmentioning
confidence: 99%
“…Neben der wiederholten Oxalat-Bestimmung im 24-Stunden-Urin empfiehlt sich bei nachgewiesener Hyperoxalurie zunächst die Bestimmung des Urin-Glykolates, um den Typ zu bestimmen (36). Als Normwert für die Urin-Glykolat-Ausscheidung werden bis 70 mg/ 1,73 m 2 Körperoberfläche/Tag angegeben.…”
Section: Kasuistikunclassified